(untitled) (Anclajes, 2021)
Federico Campbell’s interviews of authors such as Manuel Vázquez Montalbán, Juan Marsé and Félix de Azúa (among others) in Barcelona between 1969 and 1970, and the dialogue with Leonardo Sciascia (Racalmuto, 1921) have played a fundamental role in the development of Campbell’s authorial figure. His interest in Spanish and Italian writers (and more generally, in the literary tradition of the two countries) arises from his work as a journalist. However, both his early interest in Barcelona artists and his subsequent study and dissemination of Sciascia’s work reveal the development of his own work as a fictional author. Federico Campbell, seemingly through journalistic work alone, performs a metaliterary reflection and, above all, re-signifies his own work as a journalist, giving it the value of a literary learning strategy. His European travels, beyond being an important moment of dissemination for the work of certain authors, can be read a posteriori as part of an authorial strategy to re-situate himself in his own literary field.